STUDY ON CAUSE–EFFECT RELATIONS AND OPTIMIZATION OF EXEMESTANE-LOADED NANOSTRUCTURED LIPID CARRIERS - Thang, Le Quoc; Hanh, Nguyen Duc; Duong, Do Quang (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Exemestane is an anti-breast cancer drug, possesses low water solubility and low permeability. This work aimed at the cause-effect relations and optimization of exemestane-loaded nanostructured lipid carriers (EXE-NLCs) for oral delivery. Methods: Excipient screening was based on exemestane solubilities and the emulsification efficiency of surfactants. A D-optimal design based on three independent variables was applied to evaluate the cause-effect relations and optimise EXE-NLCs formulation. The particle size (PS), polydispersity index (PDI), entrapment efficiency (EE) and drug loading (DL) were investigated with respect to three independent variables including liquid lipid to total lipid ratio (X1), surfactant concentration (X2), total lipid concentration (X3). Results: EXE-NLCs were prepared by a hot sonication method employing Labrafac CC and Compritol 888ATO as liquid and solid lipids, respectively, and Cremophor RH40 as a surfactant and Lutrol E-400 as a co-surfactant. All investigated factors: liquid lipid to total lipid ratio, surfactant concentration and total lipid concentration showed significant influences on physicochemical characteristics of EXE-NLCs. The optimal EXE-NLC formulation was composed of liquid lipid to total lipid ratio (X1) of 24 % (w/w), surfactant concentration (X2) of 4 % (w/v) and total lipid concentration (X3) of 4 % (w/v). The PS, PDI, EE and DL of the optimized EXE-NLCs were found to be 41.787 nm; 0.11; 97.605 % and 1.935 %, respectively. The optimized formulation was experimentally examined which demonstrated a good agreement between experimental and predicted values. Conclusion: The cause-effect relations and optimization of EXE-NLCs were investigated and reported for the first time. EXE-NLCs formulation was successfully optimized using D-optimal design and merits further study.